Building EFL Learners’ Confidence and Belief System through Collaborative Learning: The Power of Topics of Interest - Nasmilah nasmilah (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
This paper discusses how tasks and activities in collaborative EFL learning promote learners’ confidence and belief system to perform better in their productive skills of English especially ‘speaking’. It is generally believed that learners’ lack of confidence is the main constraint when ‘speaking’ becomes the objective of an EFL lesson in addition to their lack of vocabulary and knowledge of grammar rules. Furthermore, belief system that they share as EFL learners plays crucial roles in shaping all the elements that contribute to success in EFL learning. This paper reveals (1) how tasks and activities developed by teachers at some universities in South Sulawesi build EFL learners’ confidence in speaking, and (2) how those teachers involved direct the EFL learners’ belief system to optimize the grab of English as a foreign language, the language that is believed to assist them realize their expectation to gain at least one of the widely offered scholarships, and (3) How topics of interest enhance learners’ participation in classroom that leads to success in language learning. Taking 124 students and 4 teachers from 4 universities comprising 4 classes as participants, and by utilizing several instruments such as questionnaire, interview, classroom observation and stimulated-recall, this pure qualitative study claims that teachers’ role in practicing their pre-developed activities along with the implementation of collaborative learning has greatly assisted the learners to develop stronger self- confidence and strengthen their belief system about their capability in EFL learning, especially speaking. It is also revealed that topic of interest is an essential teaching aspect which raises the awareness of the learners about the power of their metacognitive strategies in learning a second language.